Mesoscale structures in the Orinoco basin during an extreme precipitation event in the tropical Andes - Martinez, J. Alejandro; Arias, Paola A.; Dominguez, Francina; Prein, Andreas (Frontiers in Earth Science, 2024)
During the night of March 31st, 2017, a severe precipitation event affected the city of Mocoa, in the tropical Andes. Total 24-hour accumulated precipitation during that day was the fourth largest on record. Satellite data shows that the event was associated with a Mesoscale Convective System (MCS) that formed over the Amazon and moved westward, reaching the tropical Andes. Reanalysis data suggests that a rapid intensification of the Orinoco Low-Level Jet (OLLJ) traveling southwestward parallel to the Andes was a precursor that favored the zones of convergence for MCS formation. Upstream intensification of the OLLJ was evident 8 hours prior to the Mocoa precipitation event. Given the lack of a dense network of observations in this understudied region, we use the Weather Research and Forecasting model (WRF) to explore the plausible mesoscale structures in the OLLJ region associated with the initiation and development of the MCS. We study an ensemble of simulations with different grid spacings (12, 4 and 1.3 km) and Planetary Boundary Layer (PBL) schemes (YSU, MYNN and QNSE). The more realistic MCSs were obtained with the QNSE and YSU schemes, given that the corresponding simulations included a density current in the lowest levels moving parallel to the Andes, with a sharp line of convergence and large vertical velocities over the leading edge of the mesoscale disturbance. In contrast, the MYNN scheme produced a weaker OLLJ and no density current. It is suggested that the stronger vertical mixing in the MYNN scheme was associated with the vertical dilution of the OLLJ, and with a much weaker low-level traveling perturbation via the upward radiation of energy by gravity waves. Our results help to better understand flood-producing extreme events over the poorly studied Andes-Amazon region and provide the groundwork for improved predictability of such storms.